2013
DOI: 10.1111/cpsp.12048
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of informant discrepancies for the assessment of adolescent personality pathology.

Abstract: In this article, we compare the nature and function of selfparent informant discrepancies for adolescent personality pathology using two methods: standard difference scores (SDS) and polynomial regressions. In total, 489 11-to 18year-old youth (54% female) and their parents reported on youth personality pathology traits and general psychopathology. Findings supported convergence and divergence in parent-and self-reports. Potential utility of informant discrepancies also emerged, such that discrepancies on trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 43 publications
2
37
0
2
Order By: Relevance
“…This means that shared method variance may be inflating estimates of the relationship between RAgg and disagreeableness. In addition, although we know that parents can report quite accurately on their child's personality traits (Rothbart & Bates, 2006;Tackett, 2011) and RAgg (Keenan et al, 2008), it would be important to compare the information parents provide with other informants, as informant discrepancies are relatively common in personality pathology and psychopathology research in youth (De Los Reyes & Kazdin, 2004;Tackett, Herzhoff, Reardon, Smack, & Kushner, 2013). The issue of informant discrepancies has not been investigated regarding RAgg specifically, and there may be meaningful information available (i.e., those youth with poorer self-other agreement may be more adept at hiding their perpetration from adults).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This means that shared method variance may be inflating estimates of the relationship between RAgg and disagreeableness. In addition, although we know that parents can report quite accurately on their child's personality traits (Rothbart & Bates, 2006;Tackett, 2011) and RAgg (Keenan et al, 2008), it would be important to compare the information parents provide with other informants, as informant discrepancies are relatively common in personality pathology and psychopathology research in youth (De Los Reyes & Kazdin, 2004;Tackett, Herzhoff, Reardon, Smack, & Kushner, 2013). The issue of informant discrepancies has not been investigated regarding RAgg specifically, and there may be meaningful information available (i.e., those youth with poorer self-other agreement may be more adept at hiding their perpetration from adults).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Our compilation of over 50 studies of self-other agreement on personality disorder reported a range of rank-order correlation sizes from r = .12 to r = .90, with a median of r = .35 (see Table 1). There are college, clinical, and community samples presenting a range of effect sizes from small (e.g., Tackett et al, 2013;Yalch & Hopwood, 2016;Zimmerman et al, 1988) to large (e.g., Coolidge et al, 1995;Few et al, 2013;Kelley et al, 2018;Miller et al, 2011).…”
Section: Self-other Agreement On Personality Disorder: a Brief Literamentioning
confidence: 99%
“…Thus, the polynomial regression approach can generalize to examining changes in informant discrepancies over time. Further, the polynomial regression approach has been extended to understanding and interpreting informant discrepancies in other areas, including neuroscience, personality, and treatment (Fjermestad et al 2016;Meyer et al 2016;Tackett et al 2013). Other approaches possess similar capabilities and have been successfully implemented in the study of informant discrepancies.…”
Section: Importance Of Sound Approaches To Modeling Informant Discrepmentioning
confidence: 99%